Mind the gap: Deficits in fundamental disease-specific knowledge in atrial fibrillation. (1st October 2019) - LaRosa, Anna R.; Pusateri, Alexandra M.; Althouse, Andrew D.; Mathier, Abigail S.; Essien, Utibe R.; Magnani, Jared W.
Abstract: Background: Patient success with atrial fibrillation (AF) requires adequate health literacy to understand the disease and rationale for treatment. We hypothesized that individuals receiving treatment for AF would have increased knowledge about AF and that such knowledge would be modified by education and income. Methods: We enrolled adults with AF receiving anticoagulation at ambulatory clinic sites. Participants responded to survey items encompassing the definitions of AF and stroke, the rationale for anticoagulation, and an estimation of their annual stroke risk. We examined responses in relation to household income and education in multivariable-adjusted models. Results: We enrolled 339 individuals (age 72.0 ± 10.1; 43% women) with predominantly lower annual income (20–49, 999, n = 99, 29.2%) and a range of educational attainment (high school or vocational, n = 117, 34.5%). Participants demonstrated moderate AF knowledge (1.7 ± 0.6; range 0–2) but limited knowledge about anticoagulation (1.3 ± 0.7; range 0–3) or stroke (1.5 ± 0.8; range 0–3). Income was not associated with improvement in AF ( P = 0.32 for trend), anticoagulation ( P = 0.27) or stroke knowledge ( P = 0.26). Individuals with bachelor or graduate degree had greater AF (1.8 ± 0.5) and stroke (1.6 ± 0.8) knowledge relative to those with high school or vocational training (1.4 ± 0.7 and 1.2 ± 0.9; P ≪ 0.01, both estimates). Education was not associated with understanding the rationale for anticoagulation. Most participants (230, 68%) estimated their annual stroke risk as ≥15%. Conclusions: We identified consistent, fundamental gaps in disease-specific knowledge in a cohort of adults receiving treatment for non-valvular AF. Improved patient understanding of this complex and chronic disease may enhance shared decision making, patient engagement, anticoagulation adherence, and clinical outcomes in AF. Highlights: Individuals with atrial fibrillation had limited disease-specific knowledge. Most participants overestimated their risk of stroke from 15 to 50%. Deficits in patient knowledge were attenuated slightly by education but not income. Patients require enhanced AF knowledge to participate in shared decision making.